The role of reduced glutathione on oxidative stress, reticulum endoplasmic stress and glycation in human lens epithelial cell culture - Nina Handayani; Nur Permatasari; Hidayat Sujuti; Achmad Rudijanto (GarVal Editorial Ltda., 2021)
Context: Cataracts are currently the main cause of blindness worldwide. This condition caused by a low concentration of reduced glutathione (GSH) in the lens. Aims: To evaluate the effect of glutathione (GSH) on the hyperglycemia-induced oxidative stress, reticulum endoplasmic stress, and glycation in human lens epithelial cells. Methods: Human lens epithelial cells were cultured under high-glucose conditions. Malondialdehyde (MDA), protein carbonyl content (PCC), glucose reactive protein (GRP), and advanced glycation end product (AGE) were measured by enzyme-linked immunosorbent assay after 72 h of incubation for MDA, PCC, GRP and after 2 weeks incubation for AGE. Results: The MDA and PCC levels increased in response to high-dose glucose administration compared to the control group. MDA and PCC levels were decreased at all GSH doses, whereas the lowest mean MDA and PCC levels were observed at GSH doses of 10 and 100 μM, respectively. GRP levels increased after high-glucose administration as compared to the control group. Additionally, the groups co-treated with 30 and 100 μM GSH showed reduced PCC. The AGE level was reduced at all doses of GSH compared to those in the control group. Conclusions: The results suggest that GSH inhibits oxidative stress, reticulum endoplasmic stress, and AGE formation, which may lead to the progression of diabetic cataract. Additionally, GSH may maintain lens transparency by acting as an antiglycation and controlling the AGE formation.